REVOLUZIOTING SPEAKING SKILS: THE POWER OF NEURO-LINGUISTIC PROGRAMMING (NLP) FOR TENTH-GRADE STUDENTS AT SMK BINONG PERMAI AN-NURMANIYAH - Gunawan, Yudhie Indra; Rahmania, Seruni (Linguists : Journal of Linguistics and Language Teaching, 2025)
The aim of this study was to investigate whether Neuro-Linguistic Programming (NLP) was effectively used by tenth-grade students at SMK BINONG PERMAI to improve their speaking skills. NLP is a learning method that integrates language and thought processes to optimize behavior in learning. It focuses on character development through structured thinking programs that enhance communication abilities. Applying NLP to speaking skills can be an effective strategy, as it helps students gain confidence and fluency. This study employed a quantitative approach with a quasi-experimental design to assess NLP's effectiveness. The results indicated that NLP significantly improved students' speaking skills. In the experimental class, the average pre-test score was 59.5, increasing to 63.6 in the post-test. Meanwhile, in the control class, the average pre-test score was 58.2, with a post-test score of 58. The post-test t-test results showed a significant difference between the experimental and control groups. With t-count ɑ = 5% and dƒ = 60 at 2.69, compared to the t-table value of 2.00, the results confirm that NLP is highly effective. Thus, NLP is recommended for teaching speaking skills, as it fosters confidence and ease in communication. Teachers should consider NLP as a valuable strategy for language learning.